2019
DOI: 10.2147/jmdh.s228951
|View full text |Cite
|
Sign up to set email alerts
|

<p>How Effective are Mentoring Programs for Improving Health Worker Competence and Institutional Performance in Africa? A Systematic Review of Quantitative Evidence</p>

Abstract: IntroductionMentoring programs are frequently recommended as innovative and low-cost solutions, and these have been implemented in many healthcare institutions to tackle multiple human resource-related challenges. This review sought to locate, appraise and describe the literature reporting on mentorship programs that were designed to improve healthcare worker competence and institutional performance in Africa.MethodsThis review searched and synthesized reports from studies that assessed the effectiveness of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…This evaluation in four regions of Ethiopia showed that optimizing the health extension program intervention was not associated with any positive change in the health extension workers’ ability to correctly classify common childhood illnesses within the integrated community case management program. The intervention included evidence-based components that potentially could influence the quality of care provided [ 9 , 10 ]. However, when combined in the upscaled intervention, there was no effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This evaluation in four regions of Ethiopia showed that optimizing the health extension program intervention was not associated with any positive change in the health extension workers’ ability to correctly classify common childhood illnesses within the integrated community case management program. The intervention included evidence-based components that potentially could influence the quality of care provided [ 9 , 10 ]. However, when combined in the upscaled intervention, there was no effect.…”
Section: Discussionmentioning
confidence: 99%
“…Community-based interventions have the potential to reduce morbidity and mortality in children under the age of five years [ 8 ]. Performance reviews and mentoring of primary health care workers has been effective in improving the clinical management of childhood illnesses [ 9 ]. Regular supportive supervision, in-service training, and community ownerships are also interventions that potentially could improve the performance of community health workers [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Training in clinical management skills as well as the supply of equipment and pharmaceutical drugs are prerequisites for good quality services. Supportive supervision, performance reviews, and clinical mentorship may improve the quality of care provided [ 31 33 ]. In our study most health extension workers had been trained on the clinical management of sick children, but only a fifth had been trained in the past 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies, however, have evaluated the use of audit and feedback for frontline workers. For example, a performance review and mentoring intervention in Ethiopia improved both work volume and the ability of extension workers to diagnose common illnesses [ 38 ]. In Mozambique and Uganda, an intervention that included the use of smart phones to provide direct voice connections to supervisors as well as decision support and performance feedback also improved the management of common childhood illnesses [ 39 ].…”
Section: Discussionmentioning
confidence: 99%